Comparative odour analysis of natural rubber latex-based paints using olfactometer / Nur Fadhilah Idris and Asrul Mustafa - Idris, Nur Fadhilah; Mustafa, Asrul (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
Natural rubber latex based paints are water based which are devoid of solvents which emits harmful volatile organic compounds (VOCs) upon prolonged exposure. These types of water based paints are generally regarded to pose less detrimental effect to the health and environment due to minimal emission of VOCs during application. In the context of offensive smell, olfactory disturbances are rarely described in the use and application of latex based paints. Nonetheless, odour is still emitted due to the addition of various paint additives which are generally used to enhance the properties and working quality of paints, for instances viscosity enhancer, pigments, UV absorber and so forth. This paper describes the changes in odour concentration in an in-house developed latex based paint before and after incorporation of various paint additives. Using surface emission sampling technique via flux hood of stationary source of emission with subsequent dynamic olfactometry analysis, it is shown that the odour concentration increased with the presence of additives compared to pristine latex by at least 40%. The odour concentration of latex paints were much lower once applied onto substrates and further reduced by at least 33% after 14 days of application. Consequently the finding obtained from the olfactometry analysis is useful to give an additional perspective of characterisation for further development of minimum olfactory disturbance in natural rubber latex paint formulation.